Implementing Web 2.0 Design Patterns in an Institutional Repository May Increase Community Participation - Hultman Ozek, Yvonne (Evidence Based Library and Information Practice, 2011)
Objective – To investigate whether Web 2.0 can enhance participation in institutional repositories (IRs) and whether its widespread use can lead to success in this context. Another purpose was to emphasize how an IR with a Web 2.0 approach can connect individuals in their creative and intellectual outputs, no matter what form of shared material is contributed. Design – Comparative study. Setting –Two IRs at Teachers College, Columbia University, which is a graduate and professional school of education in New York City. Subjects – Students, faculty, and staff using the PocketKnowledge and CPC IRs. Methods – Cocciolo compared two different IRs called PocketKnowledge and Community Program Collections (CPC). PocketKnowledge had the following Web 2.0 design patterns: users control their own data; users should be trusted; flexible tags are preferred over hierarchical taxonomies; the attitude should be playful; software gets better the more people use it. The PocketKnowledge IR design patterns were compared with the traditional design of the CPC IR. The CRC IR organized information based on taxonomy (e.g., programs and departments), lack of user control of their own content, and centrality of authority. Data were collected during a 22-month period. The PocketKnowledge IR was studied from September 2006 to July 2008, compiling information on both contributions and contributors. Contributions made by library staff to aid availability in archival collections were excluded from the data sets, because the study was focused on community participation in the learning environment. The CPC was studied between November 2004 and July 2006. Data collected included the contributions made to the system and information on the role of the contributor (e.g., student, faculty, or staff). Main Results – Participation was much greater in the Web 2.0 system (PocketKnowledge) than in the non-Web 2.0 system (CPC). Involvement in the latter, the CPC, was noted primarily for faculty (59%), with a smaller proportion of students (11%) contributing. This trend was reversed with the Web 2.0 system, in which 79% of the contributions came from students. However, as a group, faculty were better represented than the student body as contributors to the Web 2.0 system (23% and 8% respectively). Faculty members who created an account (without contributing) represented 30% of the population. These observations suggest that Web 2.0 is attractive to students as a space to share their intellectual creations, and at the same time it does not alienate the faculty. Notwithstanding, although 31% of the student body had created a user account for PocketKnowledge, the Web 2.0 system, only 8% of the students actually contributed to this IR. The study examined only the participation rates and was not concerned with what motivated contributions to PocketKnowledge. Accordingly, the results can be extrapolated by observing that the limitation of previous IRs is that they focused primarily on the library goals of collecting and preserving scholarly work, and did not consider what prompted faculty to contribute. Despite the satisfactory participation in the two IRs of interest, the author argued that the incentive is associated more extensively with the role as teacher than with the role as researcher. This is related to the ambition of faculty to improve classroom-based experience by ensuring that their students are as engaged as possible in the teachers’ areas of expertise. In other words, a faculty contribution is motivated by knowing that students will become familiar with what is contributed. Conclusion – This study suggests that IRs can achieve greater participation by shifting the focus from the library goals to the objective of building localized teaching and learning communities by connecting individuals through their respective intellectual outputs. Creation of a system like the CPC that supports such exchange will advance library goals by storing faculty’s scholarly work, whereas Web 2.0 offers a set of approaches and design patterns for establishing systems that help promote community participation. Greater student participation in an IR may prompt increased faculty participation, because the IR will be more extensively focused on the teaching and learning community than on the research community. Thus, the major finding of the study is that greater community participation resulted from a Web 2.0 design pattern approach.